Illuminating the Frontier of Drug Discovery: Unleashing the Power of Bioinformatics for Unprecedented Breakthroughs - S. Luqman Ali; Awais Ali; Waseef Ullah; Kashif Adil; M. Usman (International Journal of Molecular Biotechnological Research, 2023)
It takes a long time and a lot of effort to discover and develop new drugs, which necessitates extensive study and testing. With the help of computational techniques and data analysis, bioinformatics has grown to be a potent tool for drug discovery in recent years, allowing researchers to find new drugs faster. In this review, we examine the role of bioinformatics in drug discovery, including the use of ligand- and structure-based drug design, virtual screening based on pharmacophore models, de novo design based on pharmacophore models, and quantitative structure-activity relationship (QSAR) models and machine learning techniques. We also talk about how important data collection from different sources, like natural and synthetic databases, is for supporting drug discovery efforts. We highlight the potential of bioinformatics to revolutionise the field of drug discovery and to hasten the creation of new medications for the treatment of a variety of diseases through an analysis of recent researc
Keywords: Bioinformatics; Data assortment; Drug discovery; Ligand-based drug design; Machine Learning; QSAR; Structure-based drug design; Virtual screening